Spontaneous synchronous synaptic calcium transients in cultured cortical neurons - Murphy, TH (J Neurosci, 1992)
The firing pattern displayed by neuronal aggregates is thought to play a key role in cortical development and physiology. In this study, we have employed optical recording of intracellular calcium to monitor activity of multiple neurons simultaneously in primary cortical cultures. With this approach, we have observed spontaneous synchronous calcium transients among adjacent cortical neurons. These transients appear to be mediated by prominent spontaneous synaptic excitation, as they are enhanced by picrotoxin, a blocker of inhibitory GABAergic transmission, and reduced by antagonism of glutamate receptors or addition of TTX. After picrotoxin treatment, the calcium transients exhibit regular frequency and amplitude, and occur in synchrony with bursts of excitatory synaptic potentials every 10–20 sec. Using electrical stimulation, we have identified a relative refractory period, extending up to 5 sec after a synchronous burst, that may play a role in cell synchronization. NMDA receptor antagonists or reduced extracellular calcium levels lower the amplitude of the calcium transients yet fail to alter their frequency, suggesting that intracellular calcium levels may not be a major determinant of burst frequency. In contrast, mild depolarization with kainic acid (0.5–1 microM) increased burst frequency up to fivefold, suggesting a critical dependence of rhythmic activity on membrane potential. Chronic blockade of electrical activity with TTX beginning a few days after plating of cultures dampens the amplitude and significantly increases the frequency of calcium transients in mature cultures. These studies demonstrate that aggregates of cultured cortical neurons express synchronous firing activity in vitro and that this network activity is dependent in part on neuronal firing during development.